Rancang Bangun Sistem Pemantauan Suhu dan Kelembaban Udara Berbasis Arduino Uno pada Kumbung Jamur Merang - Amaliah, Wenny; Putra, Guyup Mahardhian Dwi; Khalil, Fakhrul Irfan; Dewi, Endang Purnama; Sholihin, Ibadias; Hidayat, Taufiq (LPPM Universitas Mataram, 2025)
The environmental conditions of a mushroom house are a crucial factor influencing the growth of straw mushrooms, particularly in terms of temperature and humidity parameters. Therefore, it is essential to continuously monitor the environmental conditions within the mushroom house, specifically temperature and relative humidity (RH). This study aims to design a real-time temperature and humidity monitoring system based on Arduino Uno for use in a straw mushroom house. The research consists of several stages: literature review, design and assembly, programming, testing, and evaluation of testing results using the mean absolute percentage error (MAPE) method. The results show that the developed temperature and humidity monitoring system functions effectively to monitor environmental conditions within the mushroom house. The evaluation of the measurement results using the MAPE method indicates a minimum error rate for temperature and humidity measurements, with a percentage of 2.49% and 9.80%, respectively.